Structure and spectroscopy of CuH prepared via borohydride reduction. Issue 6 (1st December 2015) - Bennett, Elliot L.; Wilson, Thomas; Murphy, Patrick J.; Refson, Keith; Hannon, Alex C.; Imberti, Silvia; Callear, Samantha K.; Chass, Gregory A.; Parker, Stewart F.
Abstract : Copper(I) hydride (cuprous hydride, CuH) was the first binary metal hydride to be discovered (in 1844) and is singular in that it is synthesized in solution, at ambient temperature. There are several synthetic paths to CuH, one of which involves reduction of an aqueous solution of CuSO4 ·5H2 O by borohydride ions. The product from this procedure has not been extensively characterized. Using a combination of diffraction methods (X‐ray and neutron) and inelastic neutron scattering spectroscopy, we show that the CuH from the borohydride route has the same bulk structure as CuH produced by other routes. Our work shows that the product consists of a core of CuH with a shell of water and that this may be largely replaced by ethanol. This offers the possibility of modifying the properties of CuH produced by aqueous routes.